ANALISIS PERAN DINAS SOSIAL DALAM MENANGGULANGI GELANDANGAN DAN PENGEMIS DI IBUKOTA KABUPATEN PINRANG - Ikmal, Muh; Malik, Ihyani; Wahid, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to determine the role of the Social Service in handling homelessness through several aspects, namely planning, providing guidance, offering assistance, and delivering training. This study applies a qualitative research approach with a descriptive method in order to gain an in-depth understanding of the issues faced. The findings of the study reveal that the role of the Social Service in addressing the problem of homeless people and beggars in Pinrang Regency remains less than effective. Although the Social Service has made efforts in planning programs and activities intended to reduce the number of homeless individuals, the outcomes achieved have not met the expectations set by both the institution and the community. Furthermore, the implementation of guidance and training is still limited, resulting in inadequate empowerment for those in need. Many programs tend to be short-term and are not followed by sustainable measures to ensure long-lasting solutions. As a consequence, the number of homeless people and beggars remains significant, reflecting the gap between policy formulation and actual practice.